(3x-2)-2x=6

Simple and best practice solution for (3x-2)-2x=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-2)-2x=6 equation:


Simplifying
(3x + -2) + -2x = 6

Reorder the terms:
(-2 + 3x) + -2x = 6

Remove parenthesis around (-2 + 3x)
-2 + 3x + -2x = 6

Combine like terms: 3x + -2x = 1x
-2 + 1x = 6

Solving
-2 + 1x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 1x = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = 6 + 2
1x = 6 + 2

Combine like terms: 6 + 2 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| 3x-6(5x-5)=24 | | 6+2x-6=x-3+6x | | x*(x+7)=-21 | | 10s-6+9+10s+2= | | 200/17.1 | | a+2b=40 | | 4+3y-3=7y+17-2y | | 1/2y-5/3=-5/7 | | 3x+30=3x+6 | | 2(10x+2)-6(x+2)=-36 | | x*(x+2)=143 | | 3x+30=3x+2 | | 7x+4=2x+19l | | 5x-q=2x-7 | | y*(y+3)=88 | | -2(z+3)-z=-4(z+2) | | 60=20t+5t(2) | | f(x)=0.07(175)+0.12x | | Z^4+2*Z^2+2=0 | | 3x+.8y=5 | | Z^4+2*Z^2-2=0 | | -a+-7+-9a+-2a+-10= | | -3=5.7 | | 11-8y+16=x+12y-2x | | 5d=36.6 | | 5k-10-8k=-35 | | 30=-2+4x | | X=Y^3-14y^2+45y | | 13/3x11/5 | | 2(3x)-5=22 | | 4x^2+16*x=20 | | 324.09=9(0.08m+26.70+0.10(26.70)) |

Equations solver categories